Social Determinant in Health : Epidemiological study of communicable diseases, Demography and Mortality rate. - Dr. Sudipta Roy (Recent Trends in Infectious Diseases, 2024)
Introduction: Social Determinants of Health (SDH) significantly influence the spread and prevalence of communicable diseases. Factors such as poverty, income inequality, healthcare access, education, employment, location, and social connections shape disease transmission within populations. Additional factors like age, gender, migration, and urbanization further explain the relationship between SDH and public health. Mortality rates, including life expectancy, infant mortality, and access to clean water and sanitation, are deeply affected by these determinants. Understanding SDH is crucial in epidemiological studies to devise effective public health solutions that address health disparities and reduce disease burdens. Materials and Methods: To assess SDH, researchers use health surveys, facility records, census data, public health databases, and policy documents. These tools help to evaluate socioeconomic indicators, healthcare access, and environmental factors. Additionally, pharmaceutical interventions such as vaccines, antivirals, and antibiotics are critical in preventing and treating infectious diseases, but their availability and effectiveness are often shaped by SDH, particularly in low-income settings. Results: SDH, including income, education, and healthcare access, directly influence the prevalence of diseases like tuberculosis, HIV, and cholera. Overcrowded, unsanitary conditions in low-income areas foster disease spread, while healthcare inequities lead to delayed treatment. Vulnerable groups, such as children and the elderly, face greater risks, and urbanization often worsens health outcomes through inadequate infrastructure. Discussion: Communicable diseases thrive in low-income areas due to poverty, overcrowding, and limited healthcare access. Addressing these issues requires improving living conditions, healthcare access, sanitation, and health education. Vulnerable groups like children, the elderly, and migrants face higher risks. Investments in water, sanitation, and healthcare are crucial to reducing mortality and health disparities. Conclusion: Addressing SDH through public health policies, improved healthcare access, and tackling structural inequalities can significantly reduce communicable disease burdens, especially in vulnerable populations. Collaborative efforts between communities, public health bodies, and governments are essential to achieving long-term health improvements.
Keywords: Epidemiological Studies; Factors affecting SDH; Life Expectancy; National Health Survey; Social Determinant of Health